2,3,5,4′- Tetrahydroxystilbene-2-O-β-D-glycoside Biosynthesis by Suspension Cells Cultures of Polygonum multiflorum Thunb and Production Enhancement by Methyl Jasmonate and Salicylic Acid - Li Shao; Shu-Jin Zhao; Tang-Bing Cui; Zhong-Yu Liu; Wei Zhao (Molecules, 2012)
Friable calli of Polygonum multiflorum Thunb have been induced in MS medium supplemented with 6-benzylaminopurine (6-BA) and kinetin (KT). Suspension cultures were initiated from friable calli by inoculating calli in liquid MS medium in shake flasks in the dark and 25 °C on an orbital shaker at 100 rpm. The maximum dry weight (DW, 7.85 g/L) and 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glycoside (THSG, 56.39 mg/L) of suspension cells was obtained in MS medium after 16 days culture. Both methyl jasmonate (MeJA) and salicylic acid (SA) could increase THSG production. The most appropriate concentration of MeJA was 100 μmol/L in MS medium, in which concentration THSG content reached the maximum value of 147.79 mg/L, which represented a 162.36% increase compared to that of the control (56.33 mg/L). The most appropriate concentration of SA was 125 μmol/L in MS medium, at which concentration THSG content reached its maximum value of 116.43 mg/L, a 106.69% increase compared to that of the control (56.33 mg/L).